Circumscription of African Dipcadi (Asparagaceae, Scilloideae) species based on ITS sequence data and morphology - Chapano, Christopher; Løken, Solveig Bua; Kativu, Shakkie; Zimudzi, Clemence; Bjorå, Charlotte Sletten; Stedje, Brita (Phytotaxa, 2025)
Species circumscriptions in the genus Dipcadi were evaluated based on both morphological and molecular data, with an emphasis on African taxa. DNA was extracted and the ITS region amplified for 33 Dipcadi accessions, and an additional 18 ITS sequences were obtained from GenBank. Phylogenetic analyses based on Maximum Likelihood and Bayesian Inference were congruent. The species D. marlothii and D. glaucum are recovered as monophyletic, and their status is also supported by morphological data. Other species are either paraphyletic (D. viride), polyphyletic (D. longifolium, D. serotinum, and D. erythraeum), or in unresolved clades with other taxa (D. gracillimum and D. platyphyllum). Future studies should include additional loci and more material to improve the resolution of species relationships and to properly delimit non-monophyletic taxa.